2017
DOI: 10.14507/epaa.25.2637
|View full text |Cite
|
Sign up to set email alerts
|

Desire for democracy: Perspectives of parents impacted by 2013 Chicago school closings

Abstract: Abstract:In this article, we discuss the historical shifts in the purposes of public education and examine how neoliberal education policies, like Chicago's school closings, attempt to limit the purpose of public education to be in service to and at the whim of the market. We juxtapose this dominant neoliberal narrative of public education with the voices of the parents from closed schools, whose deep involvement with and beliefs about public schools counter neoliberalism's shallow concept of the public purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, residents often argue that these processes for "community input" are performative and that closure decisions are made with little regard for the immediate needs of those communities most affected (Buras, 2015;Freelon, 2018;Pappas, 2016). Most studies describing residents' reactions showed that, even with votes or forums or committees, community members felt excluded from closure and consolidation processes: They did not close their schools-instead, their schools closed on them (Alsbury & Shaw, 2005;Bard, Gardner, & Wieland, 2006;Buras, 2015;Chance & Cummins, 1998;Deeb-Sossa & Moreno, 2016;DeYoung, 1995;DeYoung & Howley, 1990;Ewing, 2018;Freelon, 2018;Gaertner & Kirshner, 2017;Kirshner, 2015;Lincove et al, 2017;Null, 2001;Patterson et al, 2006;Siegel-Hawley et al, 2017;Shiller, 2017;Vaughan & Gutierrez, 2017;. Residents sometimes felt unheard by school boards on the basis of racial discrimination (Briscoe & Khalifa, 2015;Desimone, 1993), and in other instances, residents contended that their schools were "set up" to fail by the district or state, whether due to inadequate resources for students with special education or language needs or to broader funding inequities (Freelon, 2018;Good, 2016;Kretchmar, 2014;Patterson et al, 2006).…”
Section: Implementation Of Closurementioning
confidence: 99%
See 1 more Smart Citation
“…However, residents often argue that these processes for "community input" are performative and that closure decisions are made with little regard for the immediate needs of those communities most affected (Buras, 2015;Freelon, 2018;Pappas, 2016). Most studies describing residents' reactions showed that, even with votes or forums or committees, community members felt excluded from closure and consolidation processes: They did not close their schools-instead, their schools closed on them (Alsbury & Shaw, 2005;Bard, Gardner, & Wieland, 2006;Buras, 2015;Chance & Cummins, 1998;Deeb-Sossa & Moreno, 2016;DeYoung, 1995;DeYoung & Howley, 1990;Ewing, 2018;Freelon, 2018;Gaertner & Kirshner, 2017;Kirshner, 2015;Lincove et al, 2017;Null, 2001;Patterson et al, 2006;Siegel-Hawley et al, 2017;Shiller, 2017;Vaughan & Gutierrez, 2017;. Residents sometimes felt unheard by school boards on the basis of racial discrimination (Briscoe & Khalifa, 2015;Desimone, 1993), and in other instances, residents contended that their schools were "set up" to fail by the district or state, whether due to inadequate resources for students with special education or language needs or to broader funding inequities (Freelon, 2018;Good, 2016;Kretchmar, 2014;Patterson et al, 2006).…”
Section: Implementation Of Closurementioning
confidence: 99%
“…However, one study described students' emotional reactions as "complicated," characterized by both a sense of loss and a feeling of opportunity (Steggert & Galletta, 2018). Several studies investigated the impacts on unstably housed students (Aviles & Heybach, 2017) and students with dis/ abilities (de la Torre et al, 2015;Graham et al, 2014;McMahon, Parnes, Keys, & Viola, 2008;Vaughan & Gutierrez, 2017), finding that these students have unique transportation and staffing needs that are often overlooked with closures.…”
Section: Impacts Of Closurementioning
confidence: 99%
“…However, according to Duncan-Shippy and colleagues, the far greatest costs of school closures include 1) the breach of public trust, 2) the subsequent threat to democracy, and 3) the continuation and reinforcement of racial and social class divisions. Posturing the closure of an elementary or secondary school as a threat to democracy may seem exaggerated, but others have made similar claims (Kretchmar, 2014;Vaughan & Gutierrez, 2017).…”
mentioning
confidence: 99%
“…However, most community members who have been directly impacted by school closures more commonly describe official request for community input as performative; little regard for the immediate needs of their community is shown across the closure process (Buras, 2015;Freelon, 2018;Pappas, 2016;Tieken & Auldridge-Reveles, 2019). Despite engaging in votes, forums and/ or committees, many community members still walk away from the closure process feeling excluded (Alsbury & Shaw, 2005;Bard, Gardner, & Wieland, 2006;Buras, 2015;Chance & Cummins, 1998;Deeb-Sossa & Moreno, 2016;DeYoung, 1995;DeYoung & Howley, 1990;Ewing, 2018;Freelon, 2018;Gaertner & Kirshner, 2017;Kirshner, 2015;Lincove et al, 2017;Lipman et al, 2014;Null, 2001;Patterson et al, 2006;Siegel-Hawley et al, 2017;Shiller, 2017;Tieken & Auldridge-Reveles, 2019;Vaughan & Gutierrez, 2017;Warner et al, 2011). These feelings of exclusion are often the result of existing racial discrimination (Briscoe & Khalifa, 2015;Desimone, 1993;Tieken & Auldridge-Reveles, 2019) such as the disparate allocation of resources to schools serving majority low-income, ELL, special education student populations (Freelon, 2018;Good, 2016;Kretchmar, 2014;Patterson et al, 2006;Tieken & Auldridge-Reveles, 2019).…”
Section: Implementation Of Closurementioning
confidence: 99%